Metabolic Dysfunction in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Not Due to Anti-mitochondrial Antibodies - Nilsson, Isabell; Palmer, Jeremy; Apostolou, Eirini; Gottfries, Carl-Gerhard; Rizwan, Muhammad; Dahle, Charlotte; Rosén, Anders (Frontiers in Medicine, 2020)
Metabolic profiling studies have recently indicated dysfunctional mitochondria in myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). This includes an impaired function of pyruvate dehydrogenase complex (PDC), possibly driven by serum factor(s), which leads to inadequate adenosine triphosphate generation and excessive lactate accumulation. A reminiscent energy blockade is likely to occur in primary biliary cholangitis (PBC), caused by anti-PDC autoantibodies, as recently proposed. PBC is associated with fatigue and post-exertional malaise, also signifying ME/CFS. We herein have investigated whether ME/CFS patients have autoreactive antibodies that could interfere with mitochondrial function. We found that only 1 of 161 examined ME/CFS patients was positive for anti-PDC, while all PBC patients (15/15) presented significant IgM, IgG, and IgA anti-PDC reactivity, as previously shown. None of fibromyalgia patients (0/14), multiple sclerosis patients (0/29), and healthy blood donors (0/44) controls showed reactivities. Anti-mitochondrial autoantibodies (inner and outer membrane) were negative in ME/CFS cohort. Anti-cardiolipin antibody levels in patients did not differ significantly from healthy blood donors. In conclusion, the impaired mitochondrial/metabolic dysfunction, observed in ME/CFS, cannot be explained by presence of circulating autoantibodies against the tested mitochondrial epitopes.